Pig regulatory macrophages as a donor-derived immune modulators in xenotransplantation - Vu, Phu Chi; Dang, Nhat Minh; Nguyen, Vinh Phuoc; Jung, Jonghyeok; Shim, Joohyun; Hwang, Jeong Ho; Hoang, Thi Xoan; Yun, Ik Jin; Kim, Jae Young (Frontiers in Immunology, 2025)
IntroductionXenotransplantation offers a potential solution to the critical shortage of donor organs; however, graft survival is limited by xeno-immune activation and coagulation dysregulation. Regulatory macrophages (Mregs) are known for their immunomodulatory capacity, yet their cross-species function in the context of xenotransplantation remains unclear. This study investigates the immunoregulatory properties of pig-derived Mregs (pMregs) as a potential donor-derived cellular therapy.MethodspMregs were generated from pig CD14⁺ monocytes using M-CSF and IFN-γ. Phenotypic characterization was performed by flow cytometry, and functional assays evaluated cytokine secretion, T-cell suppression, and induction of FOXP3⁺ regulatory T cells across pig, monkey, and human lymphocytes. An in vitro xenogeneic inflammation model was established by exposing human M1 macrophages to pig endothelial cells to assess inflammatory cytokine responses and expression of coagulation-related genes.ResultspMregs exhibited a canonical Mreg phenotype (CD14⁺CD16⁺CD163⁺PD-L1⁺DHRS9⁺CD32⁻CD169⁻) and secreted IL-10 and TGF-β. Functionally, pMregs suppressed T-cell proliferation across pig, monkey, and human species and induced FOXP3⁺ regulatory T cells. In the xenogeneic inflammation model, pMregs attenuated inflammatory cytokine production in human M1 macrophages and downregulated mRNA expression of coagulation-associated genes, including TF and PAR-1.DiscussionThese findings highlight the cross-species immunosuppressive activity and coagulation-regulatory capacity, suggesting the potential relevance to xenograft injury. pMregs may therefore serve as a promising candidate for further investigations as a donor-derived immunoregulatory cell type to complement genetically engineered pig grafts.